THE DEVELOPMENT OF HIGH PERFORMANCED CONCRETE WHEN CEMENT & SAND ARE REPLACED BY GGBS AND ROBO SAND IN VARIOUS PROPORTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Most popular and widely used building material is concrete in the field of construction. It was found suitable than any other materials and hence very important for the constructional developments. The consumption of the concrete is huge and increasing continuously all over the world. The normal concrete may not achieve the properties like uniformity and better performance hence the high performance concrete is becoming the need of time. Improvement in the quality leads to experimentation on the conventional material with addition of other materials. Addressing the problem related to the environment conservation while producing the cement is also the necessary. During the process the carbon dioxide gets produced in huge amount. Authors have concentrated on M35 concrete with part replacement of cement with Ground Granulated Blast furnace Slag (GGBS) and sand with the ROBO sand (crusher dust). The testing is carried out on the cube and cylinder to study the strength. The improvement in the sustainability of concrete by improving cement strength is the motive of the study carried out.